A214 GENETIC VARIATION IN THE FARNESOID X RECEPTOR PREDICTS CROHN'S DISEASE SEVERITY IN FEMALE PATIENTS. (26th February 2020) - Wilson, A; Wang, Q; Almousa, A; Jansen, L; Choi, Y; Schwarz, U I; Kim, R
Abstract: Background: Crohn's disease (CD) is an immune-mediated inflammatory bowel disease defined by episodes of intestinal inflammation. There is now an increasing appreciation of the bile acid-sensing nuclear receptor, FXR, as an important regulator of intestinal inflammation, intestinal permeability and response to bacterial overgrowth. Many of these processes are dysregulated in CD. It is unclear how genetic variation in FXR impacts on CD severity. FXR deficiency is rare. Loss of function mutations in FXR as contributors to CD are unlikely; however, partial loss of function of FXR may contribute to CD progression or severity. Our group demonstrated that FXR-1G>T, a SNV adjacent to the ATG start codon, is linked to reduced transactivation of FXR gene targets. We hypothesized that changes in the intestinal barrier as a result of reduced FXR expression among those who harbor the FXR-1 T allele are more likely to exhibit a severe CD phenotype compared to G (reference) allele carriers, and thereby experience a more rapid progression to surgery. Alterations in FXR activity may in part be secondary to genetic variation in the FXR gene. Aims: To evaluate FXR-1G>T as a genomic biomarker of severity in CD and propose a plausible molecular mechanism. Methods: A retrospective study (n=542) was conducted in a Canadian cohort of CD patients. Blood samples were obtained for genotypic analysis ( FXR-1G>T ), as well as determination of the FXR downstream product, fibroblast growth factor (FGF) 19. Primary outcomes included risk and time to first CD-related surgery. To better elucidate a potential molecular basis for the observed effect of FXR-1G>T genotype on CD prognosis (more frequent and early surgery) in female CD patients, we explored a connection between the estrogen receptor (ER)-mediated pathway and genetic variation in FXR using a cell-based model. . Results: The FXR-1GT genotype was associated with the risk of (odds ratio, OR=3.34, 95%CI=1.58–7.05, p=0.002) and early progression to surgery (hazard ratio, HR=3.00, 95%CI=1.86–4.83, p<0.0001) in CD. Female carriers of the FXR-1GT genotype had the greatest risk of surgery (OR=14.87 95%CI=4.22–52.38, p<0.0001) and early progression to surgery (HR=6.28, 95%CI=3.62–10.90, p<0.0001). Furthermore, women carriers of FXR-1GT polymorphism had a nearly three-fold lower FGF19 plasma concentration compared to women with wildtype FXR-1GG genotype (p<0.0001). In HepG2 cells cotransfected with estrogen receptors (ERα and β) and FXR, presence of estradiol further attenuated variant FXR activity. Conclusions: FXR-1GT is deleterious to women with CD through ER-mediated attenuation of FXR activation. Female CD FXR-1GT carriers should be considered for more aggressive medical management. Funding Agencies: CAG, CCC, CIHR